FE ISOTOPE FRACTIONATION IN IRON METEORITES: NEW INSIGHTS INTO METAL-SULPHIDE SEGREGATION AND PLANETARY ACCRETION - Williams H.M.; Markowski A.; Quitté G.; Halliday A.N.; Teutsch N.; Levasseur S. (My University, 2006)
Magmatic iron meteorites are considered to be remnants of the metallic cores of differentiated asteroids, and may be used as analogues of planetary core formation. The Fe isotope compositions (δ57/54Fe) of metal fractions separated from magmatic and non-magmatic iron meteorites span a total range of 0.39‰, with the δ57/54Fe values of metal fractions separated from the IIAB irons (δ57/54Fe 0.12 to 0.32‰) being significantly heavier than those from the IIIAB (δ57/54Fe 0.01 to 0.15‰), IVA (δ57/54Fe - 0.07 to 0.17‰) and IVB groups (δ57/54Fe 0.06 to 0.14‰). The δ57/54Fe values of troilites (FeS) separated from magmatic and non-magmatic irons range from - 0.60 to - 0.12‰, and are isotopically lighter than coexisting metal phases. No systematic relationships exist between metal-sulphide fractionation factor (Δ57/54FeM-FeS = δ57/54Femetal - δ57/54FeFeS) metal composition or meteorite group, however the greatest Δ57/54FeM-FeS values recorded for each group are strikingly similar: 0.79, 0.63, 0.76 and 0.74‰ for the IIAB, IIIAB, IAB and IIICD irons, respectively. Δ57/54FeM-FeS values display a positive correlation with kamacite bandwidth, i.e. the most slowly-cooled meteorites, which should be closest to diffusive equilibrium, have the greatest Δ57/54FeM-FeS values. These observations provide suggestive evidence that Fe isotopic fractionation between metal and troilite is dominated by equilibrium processes and that the maximum Δ57/54FeM-FeS value recorded (0.79 ± 0.09‰) is the best estimate of the equilibrium metal-sulphide Fe isotope fractionation factor. Mass balance models using this fractionation factor in conjunction with metal δ57/54Fe values and published Fe isotope data for pallasites can explain the relatively heavy δ57/54Fe values of IIAB metals as a function of large amounts of S in the core of the IIAB parent body, in agreement with published experimental work. However, sequestering of isotopically light Fe into the S-bearing parts of planetary cores cannot explain published differences in the average δ57/54Fe values of mafic rocks and meteorites derived from the Earth, Moon and Mars and 4-Vesta. The heavy δ57/54Fe value of the Earth's mantle relative to that of Mars and 4-Vesta may reflect isotopic fractionation due to disproportionation of ferrous iron present in the proto-Earth mantle into isotopically heavy ferric iron hosted in perovskite, which is released into the magma ocean, and isotopically light native iron, which partitions into the core. This process cannot take place at significant levels on smaller planets, such as Mars, as perovskite is only stable at pressures > 23 GPa. Interestingly, the average δ57/54Fe values of mafic terrestrial and lunar samples are very similar if the High-Ti mare basalts are excluded from the latter. If the Moon's mantle is largely derived from the impactor planet then the isotopically heavy signature of the Moon's mantle requires that the impacting planet also had a mantle with a δ57/54Fe value heavier than that of Mars or 4-Vesta, which then implies that the impactor planet must have been greater in size than Mars. © 2006 Elsevier B.V. All rights reserved.
Keywords: CORE FORMATION; GIANT IMPACT; IRON ISOTOPES; IRON METEORITES; MARS; MOON